Gender, Ethnicity, and Their Intersectionality in the Prediction of Smoking Outcome Expectancies in Regular Cigarette Smokers. (January 2016) - Aguirre, Claudia G.; Bello, Mariel S.; Andrabi, Nafeesa; Pang, Raina D.; Hendricks, Peter S.; Bluthenthal, Ricky N.; Leventhal, Adam M.
The current study utilized the intersectionality framework to explore whether smoking outcome expectancies (i.e., cognitions about the anticipated effects of smoking) were predicted by gender and ethnicity, and the gender-by-ethnicity interaction. In a cross-sectional design, daily smokers from the general community (32.2% women; non-Hispanic African American [ n = 175], non-Hispanic White [ n = 109], or Hispanic [ n = 26]) completed self-report measures on smoking expectancies and other co-factors. Results showed that women reported greater negative reinforcement (i.e., anticipated smoking-induced negative affect reduction) and weight control (i.e., anticipated smoking-induced appetite/weight suppression) expectancies than men. Hispanic (vs. African American or White) smokers endorsed greater negative reinforcement expectancies. A gender-by-ethnicity interaction was found for weight control expectancies, such that White women reported greater weight control expectancies than White men, but no gender differences among African American and Hispanic smokers were found. These findings suggest that gender, ethnicity, and their intersectionality should be considered in research on cognitive mechanisms that may contribute to tobacco-related health disparities.